Nuovi elementi per la ricostruzione urbanistica dell’antica Plestia - Storchi, Paolo (O T I V M, 2020)
The ancient town of Plestia stood in the plain of Colfiorito, near a church that still preserves its name, Santa Maria di Pistia. It had great importance in antiquity because the area where the centre was founded was an obligatory point of passage for the viability of the area. This town was in fact placed on a narrow strip of flat land between the Apennines and a lake now dried up. Not much is known about the urban organization of the center, in the present work we hypothesize the presence there of an amphitheater and a basilica through aerial photography analysis.